Getting to know nature - Rajala Pettersson, Carl (My University, 2024)
The population of the world is growing. Above all, it is the cities that are growing. How we use land and water, plan and build determines whether we can preserve and develop the capacity of ecosystems to deliver ecosystem services. Global warming, animal extinctions and the poisoning of nature are fundamentally about disruption of natural process or ecosystems. By planning for ecosystem services in human society, the need for technical interventions can also be reduced. Living environments with close and integrated greenery are essential for our health and well-be ing. Spending time in green environments helps to lower blood pressure, heart rate and stress levels. Despite the numerous advantages humans gain from nature, contemporary lifestyles have led to a detachment from the natural world, with a substantial increase in indoor activities. Ecosystem services can be valued in different ways. Biotope area factor is a type of semi-quan titative valuation of ecosystem services. This simplification of the work with ecosystem services has the potential to be a support for architects to evaluate design proposals from an ecosystem services perspective. The purpose of this thesis is to explore ways for sustainable expansions within cities, i.e. densi fication, in relation to urban ecosystem services and residential qualities. The thesis focuses on three ecosystem services: biodiversity, water purification and regulation and pollination. From the theory on residential qualities related to the outdoor environment and biophilic design, evaluation tools are developed. Together with the biotope area factor tool, explorations on urban components and typologies are carried out. The results of the explorations, in combination with knowledge from previous research, forms design strategies. The design strategies are put into practice in a design proposal for the densification of Nedre Norrby in Borås. The design task does also address other challenges in the city. The thesis concludes that the transformation of Nedre Norrby could contribute to ecosystem ser vices in Borås and at the same time create many residential qualities in a new mixed content and high density neighbourhood.
Keywords: Ecosystem services, residential qualities, biotope area factor, densification